Manajemen Pembelajaran BTQ Metode Iqro' di Madrasah Ibtidaiyah Muhammadiyah 03 Takerharjo - Khulaidah, Isma Wahyu; Istikomah, Istikomah; Nadlif, Ainun (Universitas Batanghari Jambi, 2024)
This research aims to determine the BTQ learning management system using the Iqra' method at Madrasah Ibtidaiyah Muhammadiyah 03 Takerharjo. This research focuses on 4 sub-topics that will be discussed, namely planning, organizing, implementing and evaluating. This research uses a qualitative descriptive research method. Data collection techniques in this research are observation, interviews and documentation. Data analysis techniques in this research include data reduction, data presentation and then drawing conclusions. The data source for this research was obtained from primary data obtained from informants when conducting observations at the research location. Meanwhile, secondary data sources were obtained from reference books and journals that have related studies. The results of this research indicate that the management mechanism at Madrasah Ibtidaiyah Muhammadiyah 03 Takerharjo has been well realized based on the learning objectives that have been set. To achieve BTQ learning management, the Iqra' method really depends on the teacher's ability to manage the learning management itself.